Analisis Surah Yasin Dalam Kajian Tafsir dan Tajahul Al-’Arif - Ivlatia, Siti Mahrami; Nadiyyana, Siti; K, Khairunnisa; Al Rasyid, Harun (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research examines Surah Yasin, known as the heart of the Quran, in the context of tafsir and the use of the rhetorical style Tajahul al-‘Arif. This Surah holds an important position in Islamic tradition, often recited on various occasions, and is considered to contain many lessons relevant to daily life. This study aims to explore how the rhetorical style of Tajahul al-‘Arif is used in Surah Yasin to emphasize moral and spiritual messages. The method applied is qualitative analysis with a tafsir approach, where the researcher examines specific verses and their interpretations by various mufassir. The analysis results show that the use of Tajahul al-‘Arif in Surah Yasin serves not only as a rhetorical tool but also as a means to strengthen the faith and awareness of the community regarding Islamic teachings. These findings are expected to contribute to a deeper understanding of Surah Yasin and its relevance in the context of religious education and community religious practices.